Interactions between livestock husbandry and cropping in a West African savanna - Powell, J.M.; Waters-Bayer, Ann (Australian Academy of Science, 1985)
Investigates the present integration of livestock and crop production; examines the influence of crop residues on animal nutrition and the use of cattle manure in cropping and regards these in the context of further socio-economic interactions between the two ethnic groups, including land sharing agreements, labour exchange, and exchange of animal and crop products.